2004
DOI: 10.1385/ep:15:1:47
|View full text |Cite
|
Sign up to set email alerts
|

Ghrelin Expression in Hyperplastic and Neoplastic Proliferations of the Enterochromaffin-like (ECL) Cells

Abstract: Ghrelin, a recently discovered peptide isolated from the gastric corpus mucosa, is believed to be important in the regulation of growth hormone secretion and has been shown to increase appetite and food intake as well. It may also have other gastrointestinal and cardiac functions. Because a cell of origin for ghrelin has not been convincingly identified in the gastric mucosa thus far, we studied the immunohistochemical expression of ghrelin in proliferative lesions of the enterochromaffin-like (ECL) cells-a ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…Dopamine, which is substantially produced in the GI tract, was demonstrated to stimulate ghrelin secretion via its D1A receptors (20). Although PACAP and PAC1 expression has not yet been identified on PD/1 cells of the gastric fundus, PAC1 receptors have been characterized on ECL cells (61), which have been shown to secrete ghrelin (48). Further knowledge on ghrelin secretion processes is currently limited due to the difficulty of pure gastric mucosa cells isolation techniques (22).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine, which is substantially produced in the GI tract, was demonstrated to stimulate ghrelin secretion via its D1A receptors (20). Although PACAP and PAC1 expression has not yet been identified on PD/1 cells of the gastric fundus, PAC1 receptors have been characterized on ECL cells (61), which have been shown to secrete ghrelin (48). Further knowledge on ghrelin secretion processes is currently limited due to the difficulty of pure gastric mucosa cells isolation techniques (22).…”
Section: Discussionmentioning
confidence: 99%
“…The expression of obestatin was positively correlated with that of ghrelin in normal and tumorous samples. An immunohistochemical study demonstrated ghrelin immunoreactivity in enterochromaffin-like cells of human stomach, and the authors speculated that gastric enterochromaffin-like cells acquired the capacity to secrete ghrelin early in their hyperplasia-neoplasia sequence (Srivastava et al, 2004). Collectively, these emerging data suggest that ghrelin gene products and their related coupled receptors may play roles (either promoting or inhibiting) in promoting tumor growth via an autocrine/paracrine pathway.…”
Section: B Anorexia and Cachexiamentioning
confidence: 99%
“…Pernicious anaemia (PA) is considered to be the end stage of type A CAG. Immunohistochemical studies have revealed ghrelin expression in gastric neuroendocrine (NE) cell hyperplasia lesions of type A CAG patients (8,9) and gastric carcinoid tumours (10), although scarce data exist about plasma ghrelin concentrations in these patients. We recently reported that DM1 patients present an increased prevalence of latent pernicious anaemia when low plasma pepsinogen I concentrations are considered the main marker of early gastric mucosa atrophy (11).…”
Section: Introductionmentioning
confidence: 99%